Effect of the implementation of Ritual Worship and School’s Organizational Culture on Students’ Learning Outcomes of SD Metta Maitreya Pekanbaru - Rosa Ria (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP) Sekolah Tinggi Ilmu Agama Buddha Smaratungga, 2022)
This study aims to determine the effect of the implementation of worship and organizational’s culture on students’ results at SD Metta Maitreya Pekanbaru. The research method used was a survey with correlation and regression analysis. The population in this study were all students of SD Metta Maitreya Pekanbaru, while the sample was taken from 146 elementary school students in grades 4, 5 and 6. Data collection was carried out by filling in the research instrument and from the value of the report card. Data analysis used descriptive statistics, Pearson's multiple correlation, determinant coefficient and regression analysis. The results of the analysis showed that there were effects of the implementation of ritual worship and organizational culture on students’ results at SD Metta Maitreya Pekanbaru. It can be seen from the test results of the coefficient of determination (R Square) of 0,083 or 8,3% variance worship and organizational culture that can be explained through learning outcome.